One hundred and eighty years of Saga pedo (Pallas, 1771) (Orthoptera, Tettigoniidae) findings in Italy diachronically revisited - P. Brandmayr; A. Mazzei; T. Bonacci; S. Surdo; B. Massa (The European Zoological Journal)
According to the most recent updates on the occurrence of Saga pedo in Italy, including observations from San Marino, 92 findings have been reported. Of these, 12 were recorded between 2000 and 2020, 26 between 1971 and 1999, and 44 were before 1970 (1855–1969). The observations of this Saginae, listed in the annexes of the Habitat Directive, referred to 18 regions (excluding Emilia Romagna and Marche) and 42 provinces. Through this work, utilizing web searches and recently published or unpublished data, we have collected information on the species’ occurrence across all Italian regions, adding 11 more provinces and 81 new findings. We put together 174 occurrence records of this insect in Italy between 1855 and 2023, dividing them into three periods: (1) before 1970; (2) 1971–1999; and (3) 2000–2023. Here, we present its diachronic distribution. Moreover, we identified an interesting relationship between limestone or dolomite bedrocks and the distribution of Saga across Italian territory, suggesting a strong calciphily in this orthopteran. Over the past 180 years, the elevation of sampling sites has also increased. The mean altitude of Saga records rose from less than 400 m to about 540 a.s.l. with its maximum known altitude in Italy increasing from 950 to over 1,200 m a.s.l. This research provides additional insights into the importance of Citizen Science in collecting ecological data, particularly for threatened species and those listed under the Habitat Directive.